Performance of viral and bacterial genetic markers for sewage pollution tracking in tropical Thailand - Watsawan Sangkaew (2022)
Identifying sewage contamination via microbial source tracking (MST) marker genes has proven useful for effective water quality management worldwide; however, performance evaluations for these marker genes in tropical areas are limited. Therefore, this research evaluated four human-associated MST marker genes (human polyomaviruses (JC and BK viruses [HPyVs]), bacteriophage crAssphage (CPQ_056), Lachnospiraceae Lachno3, and Bacteroides BacV6-21) for tracking sewage pollution in aquatic environments of Thailand. The viral marker genes, HPyV and crAssphage were highly sensitive and specific to sewage from onsite wastewater treatment plants (OWTPs; n = 19), with no cross-detection in 120 composite swine, cattle, chicken, duck, goat, sheep, and buffalo fecal samples. The bacterial marker genes, Lachno3 and BacV6-21, demonstrated high sensitivity but moderate specificity; however, using both markers could improve specificity to >0.80 (max value of 1.00). The most abundant markers in OWTP samples were Lachno3 and BacV6-21 (5.42–8.02 and nondetect–8.05 log10 copies/100 mL), crAssphage (5.28–7.38 log10 copies/100 mL), and HPyVs (3.66–6.53 log10 copies/100 mL), respectively. Due to their increased specificity, the abundance of viral markers were further investigated in environmental waters, in which HPyVs showed greater levels (up to 4.33 log10 copies/100 mL) and greater detection rates (92.7%) in two coastal beaches (n = 41) than crAssphage (up to 3.51 log10 copies/100 mL and 56.1%). HPyVs were also found at slightly lower levels (up to 5.10 log10 copies/100 mL), but at higher detection rates (92.6%), in a freshwater canal (n = 27) than crAssphage (up to 5.21 log10 copies/100 mL and 88.9%). HPyVs and crAssphage marker genes were identified as highly sensitive and specific for tracking sewage pollution in aquatic environments of Thailand. This study underlines the importance of characterizing and validating MST markers in host groups and environmental waters before including them in a water quality management toolbox.